Lesson 1: Functions as Models

A function happen to be a simple mathemical model or a piece of larger model.

Recall that a functon is just a rule or law f, that expresses the dependency of a

variable y, on another variable x.

Example 1: The cost of a pound of orange juice for three consecutuve week

is given by the table below:

The Price of Orange Juice Week Week 1 Week 2 Week 3

Cost 200 215 230

What will be the cost of a pound of orange juice be in Week 4?

Solution: The actual cost of a pound of orange juice in Week 4 will be de-

termined by a number of factors, such as orange juice production, distribution,

sales, etc. These factors are the natural law governing orange juice cost. The

recent cost of orange juice can be model as:

x= the number of weeks since Week 1

P(x) = the cost of a pound of orange juice at time x, in pesos

The table above have shown us the details: P(0) = 200, P(1) = 215, and P(2) =

230. Then summarizing this information with the function will show us: P(x)

= 200 + (15)x.

Using the model, we can deduce that P(3) = 200 +(15)(3) = 245 pesos. We can

now predict that the cost of a pound of orange juice in Week 4 will be 245 pesos.

Note that this may or may not be accurate. The model between the relation-

ship of orange juice and it’s cost is based entirely on an observation of previous

patterns.

Example 2: The populations P

B and

P

M of two colonies of penguins, along

the Broughton and Montague Island of the New South Wales, respectively, have

been successfully modeled by the following two functions:

PB (t) = 2+(0.02)

t3

,

P M (t) = (1

:1) t

where the populations are measured in thousands of pairs of penguins and t is

measured in years from the present. When are the two colonies of equal size?

1

Solution: Since both of the functions are given by algebraic representations

formulas a natural instinct might be to try to solve the problem using an alge-

braic method. In algebraic terms, the problem would be to solve the following

equation for t :

2 + (0.002)t3

= (1 :1) t

.

However, this equation does not have an algebraic solution! (And it isnt because

we just dont know how to solve it.) Algebraic methods of solution failed.

Does this mean that the problem has no solution?

Before abandoning the algebraic approach entirely, it will serve as a clue, if

not a complete solution. Notice that right now (t = 0)

PB (0) = 2+(0.002)(0) 3

= 2,

P M (0) = (1

:1) 0

= 1.

The Broughton colony currently consists of 2000 penguins to the Montague

colonys 1000. The only way the Broughton’s and Montague’s populations will

ever be equal at some point in the future is if the Montague colony outgrows

the Broughton colony. See that we must look at the long-term behavior of the

functions. It is exactly this kind of big picture for which another method – the

graphical method – is best suited.

Plot the two population functions and convert the algebraic representations

to graphical ones. Over the next 36 years, the plots are shown below: The top blue curve represents the Broughton colony. It appears that the

Broughton colony not only has a head start (observed algebraically above, but

not so apparent here), but it is also rapidly outgrowing the Montague colony.

This would seem to settle things: The Montague colony will never equal the

size of the Broughton colony. Unfortunately, this is the wrong.

2

While graphical methods are able to give the big picture of a functions behavior,

there is always the question of how big is big enough. If we had looked at the

populations for a period of time twice as long, we would have seen the following: In this view it is apparent that the Montague population does catch up with

the Broughton population, somewhere between 60 and 70 years from now. We

could now use the zooming feature on our calculator or computer to nd the in-

tersection point and get a better estimate of the time when the two populations

will be the same.

Have we found all of the solutions? You should, at least, be skeptical by now.

Perhaps a still larger viewing window would reveal that the Broughton popu-

lation eventually retakes the Montague population. Extending the time scale

farther and farther into the future, however, shows no such trend. (What does

it show?) After a bit of experimentation in this direction, we may be ready to

conclude that the populations are equal only once. Again, we would be wrong.

If we extend our models only a short time into the past, we see that the popu-

lations were also equal a little less than ten years ago. The plots look like this: Example 3: New South Wales Penguins

See previous example

3

Solution: Notice that the algebraic problem of solving

2 + (0.002)t3

= (1 :1) t

(abandoned previously) is the same as solving 2 + (0.002)t3

– (1 :1) t

= 0

That is the same as nding the root of the function f(t) = 2 + (0.002) t3

– (1 :1) t

.

Using the graphical observation that the populations appear to be equal at some

point between t = 60 and t = 70, we might use the formula for f to calculate

approximate values of f(60) and f(70):

First Iteration t 60 70

f(t) 121.52 -101.75

Since the value of the function changes sign between t = 6 and t = 70, we have

conrmed that a root lies at some point in-between. Suppose we look half way

in-between:

Second Iretation t 60 65 70

f(t) 121.52 60.88 -101.75

Then we see that the value of f changes sign between t = 65 and t = 70, and

therefore the root must lie at some point in this interval. Computing the value

half way across this new interval leads to another table entry:

Third Iteration t 60 65 67.5 70

f(t) 121.52 60.88 -5.22 -101.75

Then notice that the root is in the interval between t = 67.5 and t = 70.

The method is clear enough to keep subdividing the one interval on which f

changes sign and compute a new value for the table at the midpoint. Even-

tually, after many iterations of this simple step, we will be able to compute

the root to any degree of accuracy. This may seem tedious, but its algorithmic

nature makes it an ideal method for use on calculators or computers, which can

perform tedious calculations very quickly.

After ve more iterations, the root is bracketed between t = 67.27 and t =

67.34. We therefore, conclude that, to one decimal place, the root is at t =

67.3. This much accuracy could have been achieved fairly quickly by graphing

and zooming. Unlike graphical methods, however, there is no limit to the degree

4

of accuracy that we may obtain by using the numerical method over and over

again.

Conclusion: Good mathematical models use the strengths of one representa-

tion to make up for the weaknesses of another. Good mathematical modelers,

likewise, use the strengths of one method to make up for the anothers weak-

nesses. Whether we are modeling a simple cause and eect relationship or a

complex physical system, we must look at problems from a variety of points of

view, and make use of all of the tools that are available to us.

Example 4:

5

Lesson 2: Evaluating Functions

To evaluate a function

1.Substitute the given value in the function of x.

2.Replace all the variable xwith the value of the function.

3.Then compute and simplify the given function.

Example 1: Given the function: f(x ) = 2 x+ 1, nd f(6).

Substitute 6 in place holder x,

f(6) = 2 x+ 1

Replace all the variable of xwith 6,

f(6) = 2(6) + 1

Then compute function. f(6) = 12 + 1

f (6) = 13

Therefore, f(6) = 13. It can also write in ordered pair (6,13).

Example 2: Given the function f(x ) = x2

+ 2 x+ 4 when x= 4. Substitute

-4 in the place holder x,

f( 4) = x2

+ 2 x+ 4

Replace the all the variables with 6, f( 4) = ( 4) 2

+ 2( 4) + 4

f ( 4) = (16) + ( 8) + 4

f ( 4) = 12

Therefore, f( 4) = 12 or simply as ( 4;12) :

Example 3: Given g(x ) = x2

+ 2 x- 1. Find g(2y).

Answer in terms of y.

g(2 y) = x2

+ 2 x 1

g (2 y) = (2 y)2

+ 2(2 y) 1

g (2 y) = 4 y2

+ 4 y 1

Therefore, 4( y)2

+ 4 y 1:

6

Example 4: Given

f(x ) = 2 x2

+ 4 x- 12, nd f(2 x+ 4).

Solution:

f(2 x+ 4) = 2 x2

+ 4 x 12

= 2(2 x+ 4) 2

+ 4(2 x+ 4) 12

= 2(2 x+ 4)(2 x+ 4) + 4(2 x+ 4) 12

= 2(4 x2

+ 16 x+ 16) + 4(2 x+ 4) 12

= (8 x2

+ 32 x+ 32) + (8 x+ 16) 12

Combine like terms f(2 x+ 4) = 8 x2

+ (32 x+ 8 x) + (32 + 16 12)

= 8 x2

+ 40 x+ 36

= 2(2 x2

+ 10 x+ 9)

Therefore, f(2 x+ 4) = 2(2 x2

+ 10 x+ 9).

Example 5: Given f(x ) = x2

-x – 4. If f(m ) = 8, compute the value of m

Solution: Make the function f(x ) equivalent to f(m )

x 2

x 4 = 8

x 2

x 12 = 0

( x 4)( x+ 3) = 0

x 4 + 0; x+ 3 = 0

x = 4; x= 3

Therefore, the value of a can be either 4 or -3.

7

Exercises:

Evaluate the functions

given:

1. p(x ) = 2x + 1, nd p(-2)

2. p(x ) = 4 x, nd p(-4)

3. g(n ) = 3 n2

+ 6, nd g(8)

4. g(x ) = x3

+ 4 x, nd g(5)

5. f(n ) = n3

+ 3 n2

, nd f(-5)

6. w(a ) = a2

+ 5 a, nd w(7)

7. p(a ) = a3

– 4 a, nd p(-6)

8. f(n ) = 4 3

n

+ 8 5

, nd

f(-1)

9. f(x) = -1 + 1 4

x;

nd f(3 4

)

10. h(n) = n3

+ 6 n, nd h(4)

8

Answers in Exercises:

1. 5

2. -16

3. 198

4. 145

5. -50

6. 84

7. -192

8. 4 15

9. – 13 16

10. 88

9

Lesson 3: Operations on Functions

Let h(x) and g(x) be functions, and the operations on these two functions is

shown below:

Adding two functions as:

(h+g)(x) = h(x)+g(x)

Subtracting two functions as:

(h-g)(x) = h(x) – g(x)

Multiplying two functions as:

(h g)(x) = h(x) g(c)

Dividing two functions as:

( h g

)(x) = h

(x ) g

(x ) ; whereg

(x ) 6

= 0

Example 1:

Let f(x) = 4x + 5 and g(x) = 3x. Find (f+g)(x), (f-g)(x), (f g)(x), and ( f g

)(x).

(f+g)(x) = (4x+5) + (3x) = 7x+5

(f-g)(x) = (4x+5) – (3x) = x+5

(f g)(x) = (4x+5) (3x) = 12 x2

+5x

(f g

)(x) = 4

x +5 3

x

Example 2:

Let f(x)= 3x+2 and g(x)= 5x-1. Find (f+g)(x), (f-g)(x), (f g)(x), and ( f g

)(x).

(f+g)(x) = (3x+2) + (5x-1) = 8x+1

(f-g)(x) = (3x+2) – (5x-1) = -2x+3

(f g) = (3x+2) (5x-1) = 15 x2

+7x -2

(f g

)(x) = 3

x +2 5

x 1

Example 3:

Let v(x) = x3

and w(x) = 3 x2

+5x. Find (v+w)(x), (v-w)(x), (v w)(x), and

( v w

)(x).

(v+w)(x) = ( x3

) + (3 x2

+5x) = x3

+ 3 x2

+5x

(v-w)(x) = ( x3

) (3×2

+5x) = x3

3x 2

-5x

(v w) = ( x3

) (3×2

+5x) = 3 x5

+ 5 x4

(v w

)(x) = ( x

3 3

x 2

+5 x) = x

x 2 x

(3 x+5) = x

2 3

x +5

Example 4:

Let f(x) = 4 x3

+ 2 x2

+4x + 1 and g(x) = 3 x5

+ 4 x2

+8x-12. Find (f+g)(x),

(f-g)(x), (f g)(x), and ( f g

)(x).

10

(f+g)(x) = (4 x3

+ 2 x2

+4x+1) + (3 x5

+ 4 x2

+8x-12) = 3 x5

+ 4 x3

+ 6 x2

+12x

-11

(f-g)(x) = (4 x3

+ 2 x2

+4x+1) – (3 x5

+ 4 x2

+8x-12) = 3x 5

+ 4 x3

2x 2

-4x+13

(f g)(x) = (4 x3

+ 2 x2

+4x+1) (3 x5

+ 4 x2

+8x-12)

= 12 x8

+ 6 x7

+ 12 x6

+ 19 x5

+ 40 x4

16×3

+ 12 x2

40x 12

(f g

)(x) = (4

x3

+2 x2

+4 x+1) (3

x5

+4 x2

+8 x 12)

Example 5:

Let h(x) = 1 and g(x) = x4

x3

+ x2

-1. Find (h+g)(x), (h-g)(x), (h g)(x),

and ( h g

)(x).

(h+g)(x) = (1) + ( x4

x3

+ x2

-1) = x4

x3

+ x2

(h-g)(x) = (1) – ( x4

x3

+ x2

-1) = x4

x3

+ x2

+2

(h g)(x) = (1) (x 4

x3

+ x2

-1) = x4

x3

+ x2

-1

(h g

)(x) = 1 x

4

x3

+ x2

1

11

Exercises:

1. If h(x) = 7x+3 and g(x) = 2 x2

+1. Find (f+g)(x)

2. If f(x) = x5

-18 and g(x) = x2

– 6x + 9, what is the vaue of (g-h)(x)?

3. If t(x) = 25 x5

and s(x) = 55 x8

, what is the value of ( t s

)(x)?

4. If v(x) = x3

and w(x) = x2

+ 4, solve (v w)(x)?

5. If f(x) = 4x + 11 and g(x) = 5x + 9, nd (f+g)(x).

6. If f(z) = 7z – 4 and g(z) = z-2, nd (f-g)(x).

7. If f(x) =8 x2

-20 and g(x) =-4, nd( f g

)(x).

8. If f(x) = 2x+2 and g(x) = 9 x2

, what is the value of (f g)(x)?

9. If f(x) = 7 x2

+ 8x -3 and g(x) = 7x, solve for (f g)(x)?

10. If f(x) = 35 x8

– 45x and g(x) = 5x, what is the value of ( f g

)(x).

12

Answers to Operations on Functions Exercises:

1. 2 x2

+7x +4

2. x5

x2

+ 6x – 27

3. 5

x 11

x3

4. x5

+ 4 x3

5. 9x +20

6. 6z -2

7. 2x 2

+ 5

8. 18 x3

+ 18 x2

9. 49 x3

+ 56 x2

– 21

10.7 x7

– 9

13